Intravascular Versus Surface Cooling in Patients Resuscitated From Cardiac Arrest: A Systematic Review and Network Meta-Analysis With Focus on Temperature Feedback. Issue 6 (31st January 2022) - Ramadanov, Nikolai; Arrich, Jasmin; Klein, Roman; Herkner, Harald; Behringer, Wilhelm
Abstract : OBJECTIVE: The aim of the study was to compare the effect of intravascular cooling (IC), surface cooling with temperature feedback (SCF), and surface cooling without temperature feedback (SCnoF) on neurologic outcome and survival in patients successfully resuscitated from cardiac arrest (CA) and treated with targeted temperature management (TTM) at 32–34°C. DATA SOURCES: We performed a systematic review on Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, MEDLINE, SCOPUS, CINAHL, Web of Science, and Clinical Trials up to June 30, 2021. STUDY SELECTION: We included randomized and nonrandomized studies on IC, SCF, and SCnoF in adult humans resuscitated from CA undergoing TTM, reporting neurologic outcome or survival. DATA EXTRACTION: We performed a network meta-analysis to assess the comparative effects of IC, SCF, and SCnoF. The overall effect between two cooling methods included the effect of direct and indirect comparisons. Results are given as odds ratios (OR) and 95% CIs. Rankograms estimated the probability of TTM methods being ranked first, second, and third best interventions. DATA SYNTHESIS: A total of 14 studies involving 4, 062 patients met the inclusion criteria. Four studies were randomized controlled studies, and 10 studies were nonrandomized observational studies. IC compared with SCnoF was significantly associated with better neurologic outcome (OR, 0.6; 95% CI, 0.49–0.74) and survival (OR, 0.8; 95% CI, 0.66–0.96). IC compared with SCF, and SCF compared with SCnoF did not show significant differences in neurologic outcome and survival. The rankogram showed that IC had the highest probability to be the most beneficial cooling method, followed by SCF and SCnoF. CONCLUSIONS: Our results suggest that in patients resuscitated from CA and treated with TTM at 32–34°C, IC has the highest probability of being the most beneficial cooling method for survival and neurologic outcome.